Application of a semianalytical strain assessment and multiaxial fatigue analysis to compare rolling contact fatigue in twin‐disk and full‐scale wheel/rail contact conditions. Issue 1 (25th October 2021) - Zani, Nicola; Ekh, Magnus; Ekberg, Anders; Mazzù, Angelo
Abstract: A semianalytical model is introduced to assess rolling contact fatigue problems in railway applications. The constitutive law is based on the nonlinear kinematic and isotropic hardening model of Chaboche–Lemaitre, which allows the cyclic elastoplastic strain under the contact surface to be evaluated. The much higher computational effectiveness in comparison with finite element (FE) analyses is quantified. The Dang Van multiaxial fatigue criterion is implemented to evaluate the rolling contact fatigue in the subsurface elastic region where cracking is relatively rare but more dangerous than surface cracks. The influence of the presence of sulfides in the wheel matrix in decreasing fatigue strength is also assessed by means of Murakami's approach. The model is used to compare conditions under small‐scale twin‐disk experiments to full‐scale wheel/rail contact conditions. It is found that, for the same Hertzian pressure, the small‐scale contact is more conservative in that it causes a deeper plasticized layer as compared with the elliptical full‐scale contact. In the investigated cases, crack initiation is also not expected according to Dang Van criterion in neither of the studied contact conditions. Highlights: A semianalytical model is developed to study the rail–wheel contact problem. Full‐scale rail–wheel contact and small‐scale twin‐disk contact problems are compared. The line contact problem experiences a deeper plasticized layer. The subsurface crack initiation is assessed using the Dang Van fatigue criterion.